PROVOST’S ADMINISTRATIVE SKILLS AND TEACHER’S JOB SATISFACTION IN SHEHU SHAGARI COLLEGE OF EDUCATION, SOKOTO STATE, NIGERIA - FODIO GARBA; FALMATA ABDULKARIM GALTIMARI (International Studies Journal)
This study examined role performance of college Provost’s Administrative Skills on Teachers’ Job Satisfaction in Shehu Shagari College of Education Sokoto State, Nigeria.  The study adopts survey research design. The study population consists of 1500 academic and non-academic staff of the college, Kriejie and Morgan (1970) table for determining sample was used to arrive at a sample size of 306 respondents, which were selected using stratified and simple random sampling techniques. A structured questionnaires based on five Likert scale rating was used to collect data. Descriptive statistic was used to analyze data while corresponding hypotheses were tested at 0.05 level of significance. The result indicates that the college Provost maintains smooth human relations with teachers. The study concluded that college Provost’s, human relation with teachers can be effectively maintained through conducive and enabling working environment with zero tolerance for nepotism and if sustain will result in the attainment of organizational goals and objectives, not only in the college but at all categories of our educational institutions.